Treatment preferences and outcome in male hypogonadotropic hypogonadism: an Indian perspective. (4th September 2015) - Sanyal, D.; Chatterjee, S.
Summary: This retrospective study assessed treatment preferences and outcome with testosterone or HCG / HCG–FSH combination in Indian male idiopathic hypogonadotropic hypogonadism (IHH) subjects ( n  = 31) above 18 years of age. 38.7% of IHH study subjects had no fertility plans and chose 3 monthly intramuscular testosterone undecanoate. 73.7% of subjects with fertility plans chose human chorionic gonadotropin (HCG) alone due to cost considerations. Spermatogenesis occurred in 21.4% on HCG alone and 60% of subjects on HCG with follicle‐stimulating hormone (FSH) combination. Treatment failure is higher than published Western rates. FSH and HCG combination regimen is costly but superior to HCG alone. However, treatment failure still persists, suggesting unknown testicular defect in IHH.